TRANSFORMASI MANAJEMEN KURIKULUM PESANTREN MENUJU STANDAR PENDIDIKAN NASIONAL - Agus Prayitno; Somantri Somantri; Otty Yuliati Pramono (Universitas Islam Bunga Bangsa Cirebon, 2022)
Islamic boarding schools (pesantren) in Indonesia face the urgent imperative of aligning their curriculum management systems with the National Education Standards (SNP) while simultaneously preserving their distinctive religious and cultural identity. The integration of these dual demands requires comprehensive institutional transformation that goes beyond mere administrative compliance. This study aims to examine the process of curriculum management transformation in pesantren toward the fulfillment of national education standards, with particular attention to the organizational, pedagogical, and administrative dimensions of change. A systematic literature review methodology was employed, drawing on peer-reviewed journal articles, academic books, and official educational policy documents published between 2019 and 2024. The findings reveal that successful curriculum transformation in pesantren involves three interrelated pillars: structural reorganization of curriculum planning processes, capacity building among educators, and strategic integration of Islamic values within nationally standardized competency frameworks. Research gaps identified in prior studies indicate an insufficient focus on adaptive mechanisms that allow pesantren to negotiate compliance without compromising their ideological foundations. This study contributes a conceptual framework for understanding transformative curriculum management in Islamic educational contexts.